Conceptual models as basis for integrated information warehouse development - Roland Holten (Westfälische Wilhelms-Universität Münster, Institut für Wirtschaftsinformatik, 2001)
Research in the field of information warehousing mostly focuses technical aspects. Only recently some contributions are found dealing with methodical aspects of information warehouse development processes. With respect to the central role information warehouses play for the management a development method is presented which strictly concentrates on management views. Language concepts are developed which allow the specification of information warehouses out of the managements perspective and a representation formalism supporting this language is presented. Methodically the language construction is based on constructive philosophy. Conceptual models are used as meta information in later development phases and it is shown how meta data of etl and olap tools available on the market can be generated out of the conceptual models. The approach presented has been verified by means of a prototype.
Keywords: 650